Tectonics of the Kruta Balka ore knot of the Near-Azovian area - Shatalov, N.N. (Reports of the National Academy of Sciences of Ukraine, 2017)
The results of investigations for the large structural Kruta Balka Sorokinska graben-syncline and Near-Azovian megablock of the Ukrainian Shield are presented. The features of fault-block tectonics and its influence on forming the ore knot are defined. The Sorokinska graben-syncline and other fault zones of the orthogonal and diagonal systems and their significance in the localization of the unique Kruta Balka rare-metal deposit are characterized. The features of pegmatites and the manifestation of magmatism, metasomatism, and mineral- and ore-geneses are studied.